2017
DOI: 10.1007/s40744-017-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease and Self-Injection: Ethnographic Investigations into the Patient Experience During Treatment

Abstract: Introduction Drug administration by self-injection provides an option to treat chronic inflammatory diseases such as rheumatoid arthritis (RA) and Crohn’s disease (CD). However, a negative self-injection experience for patients may reduce patient adherence to the recommended treatment regimen. In this study, a holistic approach was used to identify common themes along the treatment pathway and at self-injection that, if changed, could improve patient experience and treatment outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 32 publications
2
65
2
Order By: Relevance
“…The results of this study revealed that, after routine training, patients generally found the CZP PFP easy to use, and patient confidence and satisfaction relating to self-injection were high. As expected, increasing self-injection experience, together with routine training and continued support from the service provider nurses, was associated with a numerical trend towards improvement in all three aspects of PEx [5,14], most notably in both confidence and satisfaction. Nevertheless, after self-injection at visit 1, levels of confidence around safe patient self-injection were higher among nurses than among the patients themselves; this suggests that some patients may initially be competent (based on nurse opinion) but lack confidence.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study revealed that, after routine training, patients generally found the CZP PFP easy to use, and patient confidence and satisfaction relating to self-injection were high. As expected, increasing self-injection experience, together with routine training and continued support from the service provider nurses, was associated with a numerical trend towards improvement in all three aspects of PEx [5,14], most notably in both confidence and satisfaction. Nevertheless, after self-injection at visit 1, levels of confidence around safe patient self-injection were higher among nurses than among the patients themselves; this suggests that some patients may initially be competent (based on nurse opinion) but lack confidence.…”
Section: Discussionsupporting
confidence: 76%
“…The CZP PFP, along with the PFS and reusable electronic injection device, allows patients to choose their preferred device. Provision of a choice of treatment devices could allow patients to align their treatment with their specific preferences and needs [14], which may improve confidence around self-injection. Previous studies have shown that innovative design of self-injection devices such as the CZP PFP can also improve patient confidence and satisfaction with self-injection [12], while the device used can influence the level of pain, ease of use, and convenience reported by patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…The second most important attribute identified in the present study was confidence that there would be no loss of product during preparation or delivery, with no difference observed between the percentage of nurses who ranked this attribute as the most important between the FPAS and SPAS (22.2% [95% CI 11.2, 37.1] and 20.0% [95% CI 9.6, 34.6]). Nurses have previously identified 'confidence that a full dose has been delivered' as the most important attribute for SSA syringes [7], and it is a concern among patients with chronic diseases who administer self-injections that product can be lost if injections are too shallow [20]. However, in the present study, 81% of nurses gave the highest rating for the statement regarding confidence of no product was lost with the LAN new syringe compared with 10% for the octreotide LAR syringe.…”
Section: Discussioncontrasting
confidence: 55%
“…Assuming price parity, the choice of biosimilar may come down to a choice of device, as this can have a potentially strong influence on adherence. It is well known across all areas of medicine that patient anxiety and fear of needles can lead to poor adherence [52][53][54]. The biosimilar pegfilgrastim considered to have the most easy-touse device, for example, with a shorter and smaller diameter or hidden needles, would likely lead to improved adherence [54].…”
Section: Assessing the Value Of Biosimilar Pegfilgrastimmentioning
confidence: 99%